Direct Reference in Natural Class Terms. Ontological Considerations - Alvarado, José (2012)
Has the theory of direct reference for general terms ontological consequences or requirements? It has normally been said that general terms should be conceived as rigid designators of “natural classes”, but this is a very vague expression. What is a “natural class” here? Is it a universal? Is it a class of resembling objects or tropes? It is argued that the theory of direct reference functions better in connection with an ontology of universals. The semantic model actually requires certain type of successful cognitive relation with the referent and it is difficult to explain how such a successful connection could be obtained if there are no universal properties, but only perfect resemblance classes of objects or tropes.